The Effect of The Corona Virus Disease of 2019 (COVID-19) Pandemic on The Learning Situation - GC, Krishna Bahadur (The Educator Journal, 2023)
The global pandemic of Corona Virus Disease of 2019 (COVID-19) adversely affected the various aspects of human life. There was a severe impact of the COVID-19 pandemic in the academic years 2076, 2077, and 2078 BS in the Nepalese education system. Though other sectors of the nation have been affected by such a pandemic, significant influence of it has been seen in the education sector. In this regard, this paper aims to explore the effect of the Corona Virus Disease of 2019 (COVID-19) pandemic on classroom instruction and to find out the challenges of virtual and face-to-face modes of school education. This research work follows qualitative design. Purposive sampling method was used to select the participants and the data were collected through open ended interviews, observation checklists, and focus group discussion. The analysis has been made in thematic way following the rigor of qualitative research. The study shows a great effects of the Corona Virus Disease of 2019 (COVID-19) pandemic on the school education of Gorkha municipality. The virtual mode of instruction has been seen less effective during COVID-19 pandemic situation in the study area. Physical classes were effectively conducted before and after the pandemic. Several challenges have been noted in the virtual mode of instruction. They include the lack of internet access, limited access to electronic devices, and a lack of electricity in the district. The findings of the study entail that the blended mode could be more suitable to the students studying in the schools of Gorkha Municipality which could create opportunities for face-to-face and virtual learning together if they can be supported with easy access to the internet and electronic devices.